การรับฟังการกระทำความผิดครั้งอื่น ๆ ของจำเลยเป็นพยานหลักฐานในคดีอาญา - ยุพดี ธรรมาภิมุขกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The evolution of fact finding is to search for the best methodology to acquire the truth that most relating to cases as much as possible and to eliminate any evidences unrelated. Evidences concerning any other previous crimes committed by the defendant are usually not considered as evidences related to the case issue, in dispute; therefore, they are not inadmissible, as evidences, in a criminal prosecution in a court of law. Thailand, before the promulgation of the Act Amending Criminal Procedure Code (No. 28), B.E. 2551, applied the exclusionary rule specifically to evidences from other crimes committed by defendant and that rule was generally accepted and openly used in Thai court; even though, it was not officially statutory law. Later, the exclusionary rule, including the exceptions, is stipulated by the Act Amending Criminal Procedure Code in order to allow the court using its discretion in refusing or admitting the evidence. In many countries, the court is increasingly agreed to use its discretion in admitting the evidence connected to the defendant’s previous crimes, however, degrees of the court’s discretion are different in each country. In some civil law countries, e.g., France, have no limitation on the court’s discretion; countries that limit the court’s discretion in admission such evidences are some common law countries, for example, the United States of America and Britain. For Thailand, the author finds that the discretion given to the Thai court in considering to admit or refuse the evidence involved with defendant’s previous crimes committed as authorized by Section 226/2, with three exceptions specified, of the Criminal Procedure Code as amended by the Act Amending Criminal Procedure Code (No. 28), B.E. 2551, are certainly insufficient, and thus the Court should be invested with more discretion. Consequently, the author suggests that the adding of more exceptions to the exclusionary rule of previous crimes committed is required in order that the evidence-admitting criteria shall be more flexible and move in the same direction.